Two new Lobane Diterpene from a Bornean Soft Coral, Sinularia sp. - Chin, Soon Phan; Shean, Yeaw Ng; Takashi Kamada; Charles Santhanaraju Vairappan (Natural Product Communications, 2015)
Two new lobane diterpenoids, prenyl-a-elemenone (1), ent-prenyl-ß-elemene (2) (stereoisomer), and a known compound, a-murrolene (3) were isolated from a population of Bornean soft coral Sinularia sp. The structures of these compounds were elucidated on the basis of spectroscopic data, including 2D NMR and HR-MS spectra. Compounds were tested for their cytotoxicity and antibacterial activities against antibiotic resistant clinical strains.